2011
DOI: 10.1002/jemt.21104
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating the pickup of individual DNA molecules by AFM nanomanipulation with tips mechanically worn on bare mica

Abstract: The tip is one of the critical factors to improve the efficiency in picking up individual DNA molecules from solid substrates based on atomic force microscope (AFM) nanomanipulation. We found that wearing AFM tips on certain solid substrates in advance to nanomanipulation operation would largely improve the pickup efficiency, which was ascribed to the increasing affinity of the tip to the DNA molecules along with the increase of the tip radius after wearing. It was demonstrated that bare mica was superior to A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…AFM offers excellent precision in positioning and manipulation, which allows users to image nanosamples during the manipulation process. However, typical AFMs have only a single probe tip as the end-effector, which leads to severely inefficient nanomanipulation. , In addition, contact-mode manipulation using a sharp, hard AFM probe might cause damage to samples and substrates. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AFM offers excellent precision in positioning and manipulation, which allows users to image nanosamples during the manipulation process. However, typical AFMs have only a single probe tip as the end-effector, which leads to severely inefficient nanomanipulation. , In addition, contact-mode manipulation using a sharp, hard AFM probe might cause damage to samples and substrates. , …”
Section: Introductionmentioning
confidence: 99%
“…30,31 In addition, contact-mode manipulation using a sharp, hard AFM probe might cause damage to samples and substrates. 32,33 Previous researchers have combined several techniques to achieve versatile nanomanipulation. Researchers have investigated the assembly of nanomaterials to AFM probes or sharp tips using tip-induced DEP, 34−37 which amply demonstrated that the nanomanipulation based on tip-induced DEP is flexible, efficient, and highly precise.…”
Section: Introductionmentioning
confidence: 99%